Relation between Mutation in BRCA1&2 Carriers and Histopathlogical Characteristics of Breast Cancer Patients in Erbil City - Hamad, Gihan H.; Ali, Salah A.; Jubrael, Jaladet M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Mutation of breast cancer susceptibility gene1( BRCA1) and breast cancer susceptibility gene2 (BRCA2) are responsible for an increased risk of developing breast cancer. This study was planned to correlate probable occurrence of sequence variant in three exons (exon 2 and exon 20) of BRCA1 and (exon 11) of BRCA2 with other clinicopathological variables like family history, grade, stage of breast cancer. Fifty breast cancer women patients which randomly selected. The age, size of tumer, grade, stage and presence of family history were measured. Pathological analysis using H and E staining method, while conventional PCR and Direct Nucleotide Sequencing Techiques were applied for detection of BRCA1 and \ or BRCA2 mutations. Molecular analysis revealed that among 50 breast cancer patient 8 of 50 harbored deleterious mutation and 9 of 50 harbored non sense mutations. The result of these experiments also revealed that there is strong relationship between mutation and each of grade and family history, but in the same time no relation was found between mutation and stage of breast cancer.
Keywords: PCR; sequencing; pathology of breast cancer